The role of a barangay high school in community improvement - Canlas, Roland Bondoc 1945-
A survey of all the 10 teachers and 100 students of the San Matias Barangay High School in Sto.Tomas, Pampanga identified school programs and activities which influence community improvement. Teachers' interest and leadership in food production projects and their membership and participation in clubs such as PTA, scouting, and subject clubs provide strong motivation for students and the community. Students engage in scouting and in economic activities like home gardening to earn while studying. Student participation in gardening, beautification, YCAP and fruit growing promote community programs.